2007
DOI: 10.1037/0022-006x.75.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of posttreatment decentering and cognitive reactivity to relapse in major depression.

Abstract: et al. (2006) demonstrated that depressed patients treated to remission through either antidepressant medication (ADM) or cognitive-behavioral therapy (CBT), but who evidenced moodlinked increases in dysfunctional thinking, showed elevated rates of relapse over 18 months. The current study sought to evaluate whether treatment response was associated with gains in decentering-the ability to observe one's thoughts and feelings as temporary, objective events in the mind-and whether these gains moderated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
161
0
10

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(181 citation statements)
references
References 55 publications
10
161
0
10
Order By: Relevance
“…Soon after, an alternative scale, the Experiences Questionnaire (EQ) was developed and it was designed to assess decentering so as to operationalize changes occurred during metacognitive-based therapies. Some studies demonstrated that EQ was capable to catch the implication of decentering in both recovery and protection against relapse in a randomized clinical trial with patients suffering MDD (Fresco, Segal, Buis, & Kennedy, 2007b;Segal et al 2006). Particularly, gains in decentering were greater in patients who responded to CBT than in those who responded to antidepressant medications; and responders to CBT with higher EQDecentering scores appeared to be more protected against further relapses.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Soon after, an alternative scale, the Experiences Questionnaire (EQ) was developed and it was designed to assess decentering so as to operationalize changes occurred during metacognitive-based therapies. Some studies demonstrated that EQ was capable to catch the implication of decentering in both recovery and protection against relapse in a randomized clinical trial with patients suffering MDD (Fresco, Segal, Buis, & Kennedy, 2007b;Segal et al 2006). Particularly, gains in decentering were greater in patients who responded to CBT than in those who responded to antidepressant medications; and responders to CBT with higher EQDecentering scores appeared to be more protected against further relapses.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It is reasonable to think that improvements in decentering may be specific to psychotherapy. Surprisingly, only few studies have addressed decentering changes, measured with EQ-Decentering, related to mindfulness interventions (Carmody, Baer, Lykins, & Olendzki, 2009, Fresco et al, 2007bTanay, Lotan, & Bernstein, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Beck (1970) described distancing as a process that allows clients to think objectively about irrational thoughts and emphasized the importance of this process for effective cognitive therapy (pp. 189 -190)-a view that many scholars have since echoed (e.g., Fresco, Segal, Buis, & Kennedy, 2007;Ingram & Hollon, 1986). The concept of distancing, although sometimes referred to as "decentering" or "self as context," is also central to many newer forms of cognitive therapy, which emphasize the importance of enhancing psychological distance from the self for allowing people to observe and accept their feelings (e.g., Hayes, Luoma, Bond, Masuda, & Lillis, 2006;Teasdale et al, 2002).…”
Section: Harnessing Language To Promote Self-regulationmentioning
confidence: 99%
“…However, it is also possible for people to self-distance to achieve other goals. For example, a person could self-distance to observe his or her feelings, an approach that mindfulness and acceptance-based therapies advocate (Bishop et al, 2004;Fresco et al, 2007;. They could also self-distance to avoid their emotions, a process that many researchers would characterize as harmful (Kenny & Bryant, 2007;Kenny et al, 2009).…”
Section: Self-distancing and Its Motivational Contextmentioning
confidence: 99%